How I discovered poetry - Nelson, Marilyn, 1946- (Dial Books, 2014)
The author reflects on her childhood in the 1950s and her development as an artist and young woman through fifty poems that consider such influences as the Civil Rights Movement, the "Red Scare" era, and the feminist movement.